UPAYA PENYELESAIAN MASALAH DUPLIKASI NOMOR REKAM MEDIS DI RUMAH SAKIT UMUM DAERAH WATES - , WENNY IRMAWATI N; , Nur Rokhman, S.Si, M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Joint Commission on Acreditation of Health Organization (JCAHO) recommends using Unit Numbering System on giving number of each patientâs medical record. However, there are still duplication problems on medical record numbers at RSUD Wates. The duplication is not only happens on one patient with more than one medical record number, but also happens on one number which is used by more than one patient. This thing will affect the retrieval of system medical record files and results in an error in practicing medical doings since the last diagnosis or the last treatment Goal: To find out the percentage of medical record number duplication case , the causes of medical record number duplication, and the effort to fix the problem of medical record number duplication at RSUD Wates. Method of research: This research is a descriptive research with qualitative approach. The research plan used is cross-sectional plan. The data in this research are collected by doing observation, interview, and documentation study of medical record procedures . The subjects of this research are registration officer and patient, while the object of this research is the data of patientâs medical record on visits during March 2014 totalling 4872 patients Result of research: According to the result of observation and documentation study, the number of patientâs medical record data during March 2014 is 4872